PELAKSANAAN PEMBELAJARAN PROGRAM PENDIDIKAN JARAK JAUH (PJJ) S-1 PGSD BERBASIS ICT FIP UNY - Hardianto, Deni (MAJALAH ILMIAH PEMBELAJARAN, 2009)
The research is aim to describe; (1) The ICT base of distance learning program implementation (PJJ S-1 PGSD) of PPSD FIP UNY from some aspects such are; (a) instructional planning (b) instructional process and (c) iinstructional evaluation, (2) The constraint factors that is faced to achieve most favorable program implementation of PJJ S-1 PGSD, (3) The instructional impact of the program to the students self motivated learning. The research method is descriptive qualitative of embedded case study research in order to gather relevan data. Data collection technique is interview, observation, and documentation. The informant is the program management, the tutor and the students of PJJ S-1 PGSD. The data is analysis with interactive model of Miles and Huberman. Data validity is obtained by conducted extensive research, persistent of observation, prolong full participation, memberchek, key informant review, and triangulation (method, data and time).The research finding is; (1) There are some paces of instructional program implementation of PJJ S-1 PGSD that are (a) training program (preparation), (b) in house tutorial, (c) self assignment by on-line, practice, and field visit, and (d) evaluation in the form of formative test, self assignment, amount of tutorial participation, and final examination (UAS). (2) The constraint factors of PJJ S-1 PGSD program implementation are: (a) dual role of the students, (b) dual role of lecture, (c) low students ICT literacy, (d) limited access to the internet, (e) students low in self motivation and achievement, and (f) limited of learning facilities. (3) instructional learning process of PJJ S-1 PGSD have no sufficient impact to the students self motivated learning, which d by; (a) limited capability of self regulation in learning such as time management, learning strategy, and important critical learning activities as reading, summarizing, note taking is not well programming, (b) low learning responsibility of the students in self evaluation, reflection, problem solving, and regulating learning process, and (c) limited learning resources utilization of the students.